Finite element analysis of failure mechanisms of ceramic coatings on metallic parts for hydrogen storage applications - Abedini, Sanam (Curtin University, 2021)
A coating system composed of a 316L stainless steel/Al2O3 functionally graded interlayer and a SiC top coat was considered for 316L stainless steel hydrogen storage containers due to promising properties of these coatings in reducing hydrogen permeation. Finite element analysis was used to investigate failure mechanisms in this system as a result of cooling from high temperature. Edge interfacial delamination and buckling driven delamination were further studied and improved by optimisation of the coating system.